Juegos verbales y el lenguaje oral en niños de la Institución Educativa Inicial N° 60748 San Pablo 2025 - Tananta Guedes, Loili (2025)
The purpose of this research was to determine the relationship between verbal icon games and oral language in children at San Pablo Early Childhood Education Institution No. 60748, during the year 2025. It was conducted using a quantitative approach, with a basic correlational design. The population consisted of 76 children from the preschool level. Observational techniques were used to collect data, using a guide validated by expert judgment. The results, obtained using Spearman's Rho statistical test, showed a correlation coefficient of 0.756 and a significance level of p = 0.05, indicating a positive, moderate, and statistically significant relationship between the variables. It is concluded that the appropriate implementation of verbal icon games directly influences the development of oral language, improving both expression and comprehension in children in early childhood education. This finding supports the importance of incorporating playful and communicative strategies from the early years of school.